Manipulation of flavour and aroma compound sequestration and release using a glycosyltransferase with specificity for terpene alcohols. (8th September 2014) - Yauk, Yar‐Khing; Ged, Claire; Wang, Mindy Y.; Matich, Adam J.; Tessarotto, Lydie; Cooney, Janine M.; Chervin, Christian; Atkinson, Ross G.
Summary Glycosides are an important potential source of aroma and flavour compounds for release as volatiles in flowers and fruit. The production of glycosides is catalysed by UDP‐glycosyltransferases (UGTs) that mediate the transfer of an activated nucleotide sugar to acceptor aglycones. A screen of UGTs expressed in kiwifruit (Actinidia deliciosa) identified the gene AdGT4 which was highly expressed in floral tissues and whose expression increased during fruit ripening. Recombinant AdGT4 enzyme glycosylated a range of terpenes and primary alcohols found as glycosides in ripe kiwifruit. Two of the enzyme's preferred alcohol aglycones, hexanol and (Z)‐hex‐3‐enol, contribute strongly to the 'grassy‐green' aroma notes of ripe kiwifruit and other fruit including tomato and olive. Transient over‐expression of AdGT4 in tobacco leaves showed that enzyme was able to glycosylate geraniol and octan‐3‐ol in planta whilst transient expression of an RNAi construct in Actinidia eriantha fruit reduced accumulation of a range of terpene glycosides. Stable over‐expression of AdGT4 in transgenic petunia resulted in increased sequestration of hexanol and other alcohols in the flowers. Transgenic tomato fruit stably over‐expressing AdGT4 showed changes in both the sequestration and release of a range of alcohols including 3‐methylbutanol, hexanol and geraniol. Sequestration occurred at all stages of fruit ripening. Ripe fruit sequestering high levels of glycosides were identified as having a less intense, earthier aroma in a sensory trial. These results demonstrate the importance of UGTs in sequestering key volatile compounds in planta and suggest a future approach to enhancing aromas and flavours in flowers and during fruit ripening.